MENINGKATKAN PERAN HAKIM - Gonzales, Marcellino (Judex Laguens, 2024)
The forum for organizing judges in Indonesia is the Indonesian Judges Association (IKAHI). IKAHI oversees the judges by carrying out a special mission and vision, which makes Indonesian judges qualified and professional so that they can synergize with the Supreme Court of the Republic of Indonesia. However, in its development, many judges have not been motivated by the role of IKAHI itself. Thus, in this article, the author focuses on the discussion of Has IKAHI as an organization carried out its role to motivate its members to realize modern justice? The discussion focuses on the theory of motivation and the organization's role in answering these questions. From the discussion, it was concluded that IKAHI had provided sufficient support for the development of modern justice, but more efforts are needed to build real motivation so that the performance of the judges who take shelter in it can grow optimally.